2013
DOI: 10.1063/1.4803080
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous p-type assignment by Hall effect measurements in annealed ZnO films grown on InP substrate

Abstract: We report on incorrect carrier type identification achieved by Hall effect measurements performed on ZnO films grown by pulsed laser deposition on InP substrates and subsequently annealed for 1 h at 600 °C in air. While Hall measurements, after post-growth annealing, reveal a change in the electrical properties of the films, from n-type to p-type, both photocurrent-based and standard C−V measurements performed on the same samples show no change in the native n-type doping of the ZnO films. A possible interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The room temperature PL spectra of the ZnO NR samples before and after plasma treatment are shown in Figure 3. The band at 380 nm (Figure 3a) corresponds to 3.26 eV energy and is associated with the ZnO band gap emission [48]. The defect emissions due to structural defects in ZnO, such as V O and Zn i , are usually located in the spectral range of 450 to 650 nm [49].…”
Section: Resultsmentioning
confidence: 99%
“…The room temperature PL spectra of the ZnO NR samples before and after plasma treatment are shown in Figure 3. The band at 380 nm (Figure 3a) corresponds to 3.26 eV energy and is associated with the ZnO band gap emission [48]. The defect emissions due to structural defects in ZnO, such as V O and Zn i , are usually located in the spectral range of 450 to 650 nm [49].…”
Section: Resultsmentioning
confidence: 99%
“…In the work presented herein, we obtained the full Cu 2 O/AZO/ZnO stack structure after a unique three-step pulsed laser deposition (PLD) process, [24][25][26][27][28][29] making the fabrication process simpler and decreasing the damage compared with other literature reports 18-23 and further improving the quality of the heterojunction in terms of the interface, surface roughness, passivation, and leakage currents. Study of the morphological, structural, optical, and electrical properties of the deposited Cu 2 O/AZO and Cu 2 O/ZnO/AZO heterojunctions revealed that the p-Cu 2 O/n-ZnO/n-AZO heterojunctions exhibited well-defined rectifying behavior and could thus be useful for future high-performance heterostructure photovoltaic devices.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Cu 2 O/AZO and Cu 2 O/ZnO/AZO heterojunctions were then deposited by PLD using a Qswitched tripled Nd:YAG laser (Quantel mod.-YG78C20, k = 355 nm). [24][25][26][27][28][29] The laser beam, with energy density of 4 J/cm 2 and repetition rate of 20 Hz, was focused at an angle of incidence of 25°1 onto the target, which was in turn placed on an x-y 121 translation system to enable uniform ablation of its 122 surface. The ZnO target (99.999% pure) and AZO 123 target (99.9% pure) were 2-inch-diameter, 0.25-124 inch-thick, sintered zinc oxide ceramic disks sup-125 plied by CERAC Inc. (USA) and PI-KEM Ltd., 126 respectively, while the Cu 2 O target was obtained by 127 cold pressing Cu 2 O powder (purity 99.99%, Sigma 128 Aldrich).…”
Section: Sample Preparationmentioning
confidence: 99%
“…These ones are partially coalesced and behave as the n-region of the heterojunction. As a p-contact, we utilised Cu instead of standard Ni/Au or Pd/Au, since the latter ones required an annealing which could cause Zn ions to migrate towards the GaN layer [32]. Both Cu/p-GaN contact resistance and Schottky barrier height are close to those of Pd/p-GaN ones [33,34].…”
Section: Methodsmentioning
confidence: 99%